Are epistemic emotions metacognitive?. (17th February 2017) - Carruthers, Peter
Abstract: This article addresses the question whether epistemic emotions (such as surprise, curiosity, uncertainty, and feelings of knowing) are in any sense inherently metacognitive. The paper begins with some critical discussion of a recent suggestion made by Joelle Proust, that these emotions might be implicitly or procedurally metacognitive. It then explores the theoretical resources that are needed to explain how such emotions arise and do their work. While there is a perennial temptation to think that epistemic emotions are somehow about the cognitive states of the person undergoing the emotion, we will see that such views can and should be resisted.